Analisis Faktor-Faktor yang Mempengaruhi Keputusan Mahasiswa dalam Memilih Studi Online Program Sarjana dan Diploma di UPBJJ Ut Jambi - Mahyudin Mahyudin; Yusrizal Yusrizal (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
The purpose of this study was to determine (1) the description of student decisions in choosing online studies at UPBJJ UT Jambi, and (2) the factors that influence student decisions in choosing online studies at UPBJJ UT Jambi. The results showed that (1) the student's decision variable in choosing online studies was in the high category with an average of 4.29 and the Respondent Achievement Level (TCR) of 85.81, (2) There were 6 (six) dominant factors that influenced the decision. students in choosing online studies, namely (a) Factor 1 which is given the identity of the Motivation, which consists of statement items F8, F9, F10, F11, and F12, (b) Factor 2 which is given the identity of the Reference Group, which consists of statement items F19 , F20, and F21, (c) Factor 3 which is given the identity of Belief and Attitude, which consists of statement items F4, F16, F17, and F18, (d) Factor 4 which is given the identity of Economic State, which consists of statement items F3, F5, and F6, (e) Factor 5 which is given the identity of Perception, which consists of statement items F14, F15, and F26, and (f) Factor 6 which is assigned the identity of Role and Status, which consists of statement items F23, F24, and F25.